Effect of collagen on large traumatic perforation of tympanic membrane - Velmurugan, Dinesh; Ghosh, Puja; Kurian, Andrew Thomas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Traumatic perforation of the tympanic membrane (TPTM) is often encountered in primary care or in the emergency department (ED). Despite several therapeutic and surgical interventions have been described in the literature, but the conservative approach of follow-up until spontaneous recovery is the most common choice.1 We investigated the utility of bovine collagen extraction patching in the large traumatic TM perforation gives better resultthan spontaneous recovery.